Comparative Genome Organization of Human, Murine, and Feline MHC Class II Region - Yuhki, Naoya; Beck, Thomas; Stephens, Robert M.; Nishigaki, Yoko; Newmann, Kymberly; O'Brien, Stephen J. (Genome Research, 2003)
To study comparative molecular dynamics in the genesis of the major histocompatibility complex (MHC), we determined a complete nucleotide sequence spanning 758,291 bp of the domestic cat (Felis catus) extended and classical class II region. The feline class II MHC includes 44 genes (31 predicted to be expressed) which display DNA sequence homology and ordered gene synteny with human HLA and mouse H2, in extended class II and centromere proximal regions (DM to DO) of the classical class II region. However, remarkable genomic alterations including gene gain and loss plus size differentials of 250 kb are evident in comparisons of the cat class II with those of human and mouse. The cat MHC lacks the entire DQ region and retains only relict pseudogene homologs of DP genes, compensated by expansion and reorganization of seven modern DR genes. Repetitive gene families within the feline MHC comprise 35% of the feline MHC with very different density and abundance of GC levels, SINES, LINES, STRs, and retro-elements from the same repeats in human and mouse MHC. Comparison of the feline MHC with the murine and human MHC offers a detailed view of the consequences of genome organization in three mammalian lineages.